ANALISIS KESULITAN DALAM PEMBELAJARAN KONSEP MEAN, MEDIAN, DAN MODUS PADA PESERTA DIDIK SEKOLAH DASAR - Rahayu, Suwasti; Ummie Masrurah; Slamet, Slamet; Budi Murtiyasa; Sumardi, Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to describe the difficulties of students in learning mathematics in statistical material, especially those related to the mean, median and mode. Researchers are also trying to find alternative solutions to overcome the difficulties faced by students. The subjects in this study were students of class 6 SD Negeri 03 Buran, Kecamatan Tasikmadu, Kabupaten Karanganyar as many as 22 students who were selected purposively. This type of research is descriptive qualitative. Data were obtained from observations, interviews and documentation with two categories of difficulty, namely those related to understanding the concept and its application to the mean, median, and mode formulas. Based on the results and discussion, it was concluded that there were two difficulties experienced by students in statistical material. Students still have difficulty understanding the concept of mean, median, mode, and difficulty in applying the formulas for mean, median and mode to the data presented in tabular form. To overcome the difficulties of students in understanding the concept of mean, median and mode, the teacher should explain the definitions and uses of the three by involving students directly in constructing the formula. Meanwhile, to overcome students' difficulties in applying the mean, median and mode formulas in tabular form, teachers are expected to be able to explain additional tables, namely frequency multiplied by data (f.x) and cumulative frequency to make it easier to find the mean, median and mode.